2021
DOI: 10.1016/j.jviromet.2021.114302
|View full text |Cite
|
Sign up to set email alerts
|

Alternative RNA extraction-free techniques for the real-time RT-PCR detection of SARS-CoV-2 in nasopharyngeal swab and sputum samples

Abstract: Standard diagnoses of SARS-CoV-2 infections are done by RNA extraction and real-time RT-PCR (rRT-PCR). However, the need for RNA extraction complicates testing due to increased processing time, high cost, and limited availability of commercial kits. Therefore, alternative methods for rRT-PCR detection of SARS-CoV-2 without RNA extraction were investigated. Nasopharyngeal and sputum samples were used to compare the sensitivity of three techniques: Trizol RNA extraction, thermal shock, and the direct use of samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, this approach results in reduced sensitivity and specificity of the downstream RT-PCR process. It may require an additional 3 to 7 PCR cycles to reach the detection threshold compared to that of reactions with purified RNA 2,12 , compromising the detection of low viral loads. Still, studies reported sensitivity values ranging from 51% 38 to 91.4% 48 as commonly used measures of validity, including specificity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this approach results in reduced sensitivity and specificity of the downstream RT-PCR process. It may require an additional 3 to 7 PCR cycles to reach the detection threshold compared to that of reactions with purified RNA 2,12 , compromising the detection of low viral loads. Still, studies reported sensitivity values ranging from 51% 38 to 91.4% 48 as commonly used measures of validity, including specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy [2], Sensitivity [3] and Specificity [4] were estimated for diagnostic efficiency as indexes using a confusion matrix approach [60][61][62] . The confusion matrix and confidence interval (95%) were calculated using a diagnostic test evaluation software MedCalc version 20.027 (MedCalc Software Ltd, Ostend, Belgium).…”
Section: Rna Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited and inconsistent access to reagents for viral RNA extraction has resulted in the development of extraction-free methods for SARS-CoV-2 molecular detection. Such protocols utilize modified thermocycling conditions and additional master mix reagents to provide direct specimen testing, which is facilitated by relatively inhibitor-free primary clinical specimens [12][13][14][15][16]. While such techniques require less dedicated consumables and processing time, resulting nucleic acids cannot be applied to downstream molecular characterization of SARS-CoV-2 variants or further workup of negative cases.…”
Section: Plos Onementioning
confidence: 99%